Comparing of educational programs in terms of achievement of competencies and learning outcomes of compulsory educational components - Омельчук, Л. Л.; Русіна, Наталія Геннадіївна (Київський національний університет імені Тараса Шевченка, 2021)
The most important elements of educational programs are the educational components (disciplines), as well as the competencies and learning outcomes they provide. The article presents a comparative analysis of some compulsory disciplines of the educational and professional program "Informatics" of the first (bachelor's) level of higher education in the field of knowledge 12 "Information Technology", specialty 122 "Computer Science" with disciplines of educational and professional programs of the same level and specialties of other institutions of higher education. The work analyzes the educational and professional program "Computer Science" of the first (bachelor's) level of higher education in the specialty 122 "Computer Science". It is implemented by the Faculty of Computer Science and Cybernetics of Taras Shevchenko National University of Kyiv in terms of comparing compulsory educational components educational-professional program "Informatics" and provided (achievable) standard learning outcomes and competencies with compulsory educational components of other educational programs. Pages of the article in the issue: 129 - 136 Language of the article: Ukrainian
Keywords: computer science; database management system; educational components; standard of higher education; educational program; комп’ютерні науки; інформатика; система керування базами даних; освітні компоненти; стандарт вищої освіти; освітня програма